2012
DOI: 10.11564/26-2-213
|View full text |Cite
|
Sign up to set email alerts
|

School enrollment in the Democratic Republic ofthe Congo: family economic well-being, gender, andplace of residence

Abstract: This paper examines school enrollment of youth in the Democratic Republic of the Congo (DRC), to identify the roles of family economic well-being

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Youth who were not children of the head of the household were also less likely to have ever attended school or to have been enrolled in the previous year, and likewise less likely to have been currently enrolled. These findings conform to other research suggesting that children of the household head are more likely to enter and to be in school than children who have been fostered into the household (Sibanda, ; Mabika and Shapiro ).…”
Section: Results Of Multivariate Analysessupporting
confidence: 90%
See 2 more Smart Citations
“…Youth who were not children of the head of the household were also less likely to have ever attended school or to have been enrolled in the previous year, and likewise less likely to have been currently enrolled. These findings conform to other research suggesting that children of the household head are more likely to enter and to be in school than children who have been fostered into the household (Sibanda, ; Mabika and Shapiro ).…”
Section: Results Of Multivariate Analysessupporting
confidence: 90%
“…Delayed entry to school is more common in rural areas and also among the youth, rural and urban, from families of lower economic well‐being (Mabika and Shapiro, ). And this delayed entry is one factor contributing to children being older than they should be for their grade in school.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research concerning gender in sub-Saharan Africa has consistently found females to be at a disadvantage [3,14,15,16]. The causes of this effect are explained variously by entrenched gender roles, cultural norms, religion, and the domestic workload of women.…”
Section: Theory and Relevant Literaturementioning
confidence: 99%
“…The presence of a male pensioner, a critical source of financial support, has also been linked to higher educational achievement for girls but not for boys (Hamoudi and Thomas 2005). At the same time, girls in very large households (Mabika and Shapiro 2012), or in households with many young children (Lindskog 2013), have lower educational achievement and school attendance than boys, possibly due to resource constraints and son preference. Finally, work done in rural South Africa suggests even greater nuance when unpacking the effects of household composition on education.…”
Section: Introductionmentioning
confidence: 99%